PENGARUH KUALITAS PELAYANAN DAN PERSEPSI HARGA TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI - Kusna, Chotimatul; Utami, Datien Eriska (Politeknik Negeri Ambon, 2025)
Introduction: This study aims to analyze the role of customer satisfaction as a mediator between the effects of service quality and price perception on Batik Solo Trans customer loyalty in Surakarta City.Methods: This research uses a quantitative approach. The population in this study was all users of Batik Solo Trans (BST) public transportation services in Surakarta City. Data collection techniques through questionnaires. The data analysis technique used in this research is path analysis. The data were processed using SmartPLS v.3.Results: Service quality has a significant effect on customer satisfaction. Price perception has no significant effect on customer satisfaction. Service quality has a significant impact in customer loyalty. Price perception has no significant effect on customer loyalty. Customer satisfaction has a significant impact in customer loyalty. Customer satisfaction mediates the effect of service quality on customer loyalty. Customer satisfaction does not mediate the impact of price perception on customer loyalty. Keywords: Service Quality, Price Perception, Customer Satisfaction, Customer Loyalty